Penerapan Metode Simple Additive Weighting (SAW) untuk Menentukan Pembimbing Skripsi - Kuswanto, Joko; Dapiokta, Jum; Agustin Muris, Anggraeni; Pebriantika, Leni (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
The selection of thesis supervisors at Universitas Baturaja is currently based on student proposals. This process is typically conducted manually and lacks a computerized system. Additionally, the assignment of thesis supervisors often overlooks the workload balance, resulting in an uneven distribution of supervisory duties among lecturers and sometimes misaligning with their areas of expertise. Given these challenges, a decision support system is needed to facilitate the selection process for thesis supervisors. This study aims to apply the Simple Additive Weighting (SAW) method to the selection of thesis supervisors. Based on the calculations, the application of the SAW method evaluates four criteria: education, academic rank, field of expertise, and supervisory workload. The final assessment results indicate that the highest score, 88.8, was achieved by Alternative 5, Hendra.